2016
DOI: 10.3892/ol.2016.4284
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cytokine-induced killer cells on immune function in patients with lung cancer

Abstract: Abstract. Cytokine-induced killer (CIK) cells have been used as adoptive immunotherapy in cancer. The present study evaluated the effect of CIK cells on immune function in patients with lung cancer. Patients were divided into three groups, according to the treatment received prior to CIK cell treatment: CIK group (no prior treatment), Che-Sur group (prior chemotherapy and surgery) and Che-Rad group (prior chemotherapy and radiotherapy). Following treatment, the average percentage of cluster of differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
3
1
Order By: Relevance
“…Many studies including our study found that the average percentage of CD3 + CD4 + , CD3 + and NK T-cells, as well as the levels of IFN-γ following several treatment courses, were significantly higher than the values observed prior to CIK cells treatment [50][51][52]. Of course, there are studies found that there are no changes after CIK cells treatment [25].…”
Section: Immunoregulation Of Cik Cells Treatment In Nsclc Patients 2contrasting
confidence: 40%
See 1 more Smart Citation
“…Many studies including our study found that the average percentage of CD3 + CD4 + , CD3 + and NK T-cells, as well as the levels of IFN-γ following several treatment courses, were significantly higher than the values observed prior to CIK cells treatment [50][51][52]. Of course, there are studies found that there are no changes after CIK cells treatment [25].…”
Section: Immunoregulation Of Cik Cells Treatment In Nsclc Patients 2contrasting
confidence: 40%
“…Otherwise, the treatment done before CIK cells treatment may affect the immune status of NSCLS patients [50]. Thus, the treatments administered to the patients prior to CIK cells therapy seemed to affect the outcome, since more courses were required to achieve effective antitumor immune responses.…”
Section: Immunoregulation Of Cik Cells Treatment In Nsclc Patients 2mentioning
confidence: 99%
“…CIK cells are mononuclear cells that can be isolated from peripheral blood or cord blood. The cells are cultured with various cytokines and are CD3 + CD56 + (48). Due to the expression of CD3 and CD56 on the cell surface, CIK cells not only demonstrate anti-tumor activity, but also have non-major histocompatibility complex-restricted killing activity (49).…”
Section: Discussionmentioning
confidence: 99%
“…The role of cytokines in cancer immunization and carcinogenesis has been recognized [ 7 ]. Many studies of cytokine polymorphisms associated with susceptibility to [ 8 , 9 ], liver cancer [ 10 , 11 ], lung cancer [ 12 ], prostate cancer [ 13 ] and ovarian cancer [ 14 ] are mixed.…”
Section: Introductionmentioning
confidence: 99%